Pengaruh Waktu Fermentasi Sari Kulit Buah Naga Merah (Hylocereus polyrhizus) Terhadap Total Bakteri Asam Laktat (BAL): Effect of Fermentation Time of Red Dragon Fruit Peel Juice (Hylocereus polyrhizus) on Total Lactic Acid Bacteria (LAB) - Aprilia Wulandari; M. Arifuddin; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Fermentation process decomposes lactose into lactic acid and various other components with success parameters seen from the pH value and Total Lactic Acid Bacteria. The purpose of this research is to analyze the effect of the fermentation time of the Red Dragon Fruit peel extract on the pH value and lactic acid bacteria. The method includes the process of extracting samples and pasteurizing the juice and then proceeding with fermentation with variations of 3, 4, 5, and 6 days at 37ºC. In addition, the extract was prepared into a test solution with graded dilutions for further testing of totaled LAB using the Total Plate Count (TPC) method. The best pH value is showing in the 5-day fermentation time, which is 3.82 and the best LAB value is showing in the 6-day fermentation time, which is 18 x . The results showed that the time of fermentation affected the pH and LAB value.